Enhancing the Competence of Mathematics Education Lecturers Based on Career Development - Masduki, Lusi Rachmiazasi; Raharjo, Tri Joko; Widodo, Joko; Prihatin, Titi (The Journal of Educational Development, 2017)
Being aware that the existence of a lecturer is important and it supports the enhancement of an institution, it is necessary to support and improve the competence of the lecturers in it. Besides fulfilling the need for promotion and functional positions, lecturers’ competency improvement also functions to increase their self-existence expected to provide impact in improving the quality of the institution. It is ironical when a leader expects that the institution he/she leads is idolized by its community but he/she has not given maximal career development to its lecturers. Research and Development method aims to produce a guide along with its test for its effectiveness. The result of the preliminary study shows that the mathematics education lecturers in the Distance Learning Program Unit of Semarang (UPBJJ-Semarang) require an opportunity to improve the competence of its lecturers through a further education and training program. It requires motivating and strengthening supervision and regulation. The results of the development show that lecturers need career development, further study, and opportunities to attend various education and training programs that support the improvement of the competence which is relevant to the field of study. As a mathematics education lecturer who has a basic soft skill in logical and systematic mindset, he/she needs to develop so as to be equivalent to the advancement of science. Based on these results, career development can be focused on thinking processes that are classified on the basis of personality types. The improvement of soft skills with the different personality types will provide an effect on the different personal and interpersonal behaviors and will be an important element in the enhancement of the lecturer's performance in mathematics education.